2020
DOI: 10.1186/s12913-020-05638-z
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in health service delivery under public-private partnership in Tanzania: stakeholders’ views from Dar es Salaam region

Abstract: Background: Public-private partnership in the health sector was introduced to improve the delivery of health services in Tanzania. Contrary, the expected outcomes have not been fully realised. This study aimed at investigating challenges encountered in implementing public-private partnership institutional arrangements in health service delivery in Kinondoni Municipality, Dar es Salaam, Tanzania. Methods: A qualitative case study design was employed, where in-depth interviews with stakeholders were held and doc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Hence, it is concluded that both the Covid-19 cases and deaths are hazardous to the SSX closing index. Our empirical results are consistent with Nuhu et al (2020) study that COVID-19 negatively influences the stock market.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Hence, it is concluded that both the Covid-19 cases and deaths are hazardous to the SSX closing index. Our empirical results are consistent with Nuhu et al (2020) study that COVID-19 negatively influences the stock market.…”
Section: Resultssupporting
confidence: 92%
“…Also, the default probability of these institutes has been substantially increased whilst the capital adequacy has been considerably reduced. Nuhu et al (2020) observed the Covid-19 impact on China and the USA's stock markets. They used a simple regression model using the SSX time series data as a sample data for China, whilst Dow Jones was a sample indicator for the USA.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As the PPPs create new structures it requires trained people to govern, monitor and evaluate them (54). In India, with inadequate human resources and capacity, state and district healthcare authorities could do little to address the regulatory issues of PPP projects (46,51).…”
Section: Public-private Partnerships During Covidmentioning
confidence: 99%
“…Indeed, a lack of leadership and unclear inter-institutional arrangement are recognised barriers to ineffective PPP. [40] In most published examples for adult-focussed PPP in the Asia Pacific region, the government had a lead role in coordination and management of the partnership, with core responsibilities specified at national, district and local level. However, there were examples of coordination being provided by NGOs acting as intermediaries between the public and private sectors, drawing on their greater management expertise and capacity.…”
Section: Discussionmentioning
confidence: 99%